The role of metacognitive strategies in planning and conducting investigative actions when investigating criminal offenses in the field of public procurement - K. B. Shnaider; B. B. Teplytskyi (Науковий вісник Ужгородського національного університету. Серія Право)
The article analyzes the role of metacognitive strategies that allow investigators to critically evaluate, plan and correct their own cognitive processes during investigations. It is characterized how, at the initial stages of the investigation, metacognition contributes to a detailed assessment of primary data initiated on the basis of documentary audits. The process of forming investigative versions that adapt to dynamically changing circumstances of the case and require investigators to have a flexible approach is considered.